Dual pathways of aging stereotype threat at work: impacts on work behaviors of older workers - Liu, Lidan; Wang, Zhongjun; Guo, Xicheng; Li, Sulei; Wu, Xiaodi (Frontiers in Psychology, 2025)
Aging stereotype threat is a significant issue in modern workplaces, affecting older workers’ self-perceptions and work behaviors. Although research often highlights the negative impacts of aging stereotypes, the dual pathways by which these stereotypes influence negative and positive work behaviors remain underexplored. This study aims to address this gap by employing a dual mediation model, grounded in Uncertainty-Identity Theory and Psychological Reactance Theory, to explore the effects of aging stereotype threat on older workers’ behaviors. Using structural equation modeling (SEM) with two-wave data from older employees in various industries, the study shows that aging stereotype threat significantly affects aging identity, which fully mediates its link to work withdrawal behaviors. In contrast, psychological reactance emerges as another mediator, leading to proactive work behaviors. The results also suggest that older workers with high self-efficacy exhibit a stronger relationship between stereotype threat and aging identity. This research adds to the literature by exploring how aging stereotype threat leads to both negative and positive behavioral outcomes. It provides valuable insights for organizations aiming to support older employees in the workplace.